2008
DOI: 10.1001/archpedi.162.12.1169
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Forced Expiratory Volume in 1 Second/Forced Vital Capacity vs Percentage of Predicted Forced Expiratory Volume in 1 Second for the Classification of Asthma Severity in Adolescents

Abstract: The majority of asthmatic adolescents have normal lung function despite experiencing significant asthma symptoms. Adding FEV(1)/FVC to symptom history changes the distribution of severity; however, both percentages of predicted FEV(1) and FEF(25%-75%) have little added effect in assessing asthma severity in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
5
24
0
Order By: Relevance
“…In many but not all of these studies, nonspecific hyperresponsiveness decreased after the intervention, consistent with a salutary effect of HACT on asthma. Another potential limitation in our study is the use of FEV1 as an end-point in children because it may be a poor measure of asthma control, especially in those of younger age [41,42]. Nevertheless, HACT has been used as ancillary treatment for asthma in the paediatric population, as the number of publications included in this analysis indicate.…”
Section: Discussionmentioning
confidence: 99%
“…In many but not all of these studies, nonspecific hyperresponsiveness decreased after the intervention, consistent with a salutary effect of HACT on asthma. Another potential limitation in our study is the use of FEV1 as an end-point in children because it may be a poor measure of asthma control, especially in those of younger age [41,42]. Nevertheless, HACT has been used as ancillary treatment for asthma in the paediatric population, as the number of publications included in this analysis indicate.…”
Section: Discussionmentioning
confidence: 99%
“…Poor asthma control is associated with reduced lung function, increased risk of exacerbations and elevated FeNO [64,65,[73][74][75][76][77]. Changes in composite measures of asthma control reflect changes in the overall clinical assessment of asthma control by healthcare providers, changes in QoL, and the need to step up or step down therapy, suggesting that these composite measures have criteria validity [78,79].…”
Section: Clinical Tools: Symptoms Exacerbations and Qolmentioning
confidence: 99%
“…These differences are not unexpected, as a number of published studies showed that individual parameters of prebronchodilator spirometry were normal in the majority of children and adolescents with asthma. On the other hand, FEV 1 /FVC as an indicator of airflow limitation is more reliable as it declines with increasing asthma severity [36,37]. However, it is still possible that the observed differences were due to technical errors in performing spirometric measurements in the controls.…”
Section: Discussionmentioning
confidence: 99%